The Economic Impact of the 2014 Ebola Epidemic : Short and Medium Term Estimates for Guinea, Liberia, and Sierra Leone - World Bank (Washington, DC, 2014)
The 2014 outbreak of the Ebola Virus Disease in West Africa has taken a horrible human toll. Although the outbreak originated in rural Guinea, it has hit hardest in Liberia and Sierra Leone, in part because it has reached urban areas in these two countries, a factor that distinguishes this outbreak from previous episodes elsewhere. As of September 10, 2014, there had been 2,281 recorded deaths out of 4,614 suspected or confirmed cases of Ebola. Experts fear that the true numbers may be two to four times larger, due to underreporting. Misery and suffering have been intense, especially in Liberia where doctors have had to turning patients away for lack of space in Ebola treatment centers. Inevitably, before the outbreak is contained the human impacts will increase considerably over these numbers. Epidemiological estimates are acknowledged as highly uncertain and are not the subject of this note. What is certain is that limiting the human cost will require significant financial resources and a concerted partnership between international partners and the affected countries. Particularly in Liberia and Sierra Leone, government capacity is already overrun and the epidemic is impacting macroeconomic activity and budgetary resources. This note informs the response to the epidemic by estimating these macroeconomic and fiscal effects. Any such exercise is necessarily highly imprecise due to limited data and many uncertain factors, but it is still necessary in order to plan the economic assistance that must accompany the immediate humanitarian response. The goal is to help affected countries to recover and return to the robust economic growth they had experienced until the offset of this crisis.